An overview of solar/visible light-driven heterogeneous photocatalysis for water purification: TiO2- and ZnO-based photocatalysts used in suspension photoreactors - Khatcharin Wetchakun (2019)
© 2018 The Korean Society of Industrial and Engineering Chemistry Heterogeneous photocatalysts are able to be prepared with various methods and are allowed to modify to improve photocatalytic efficiency. In this review, we evaluate current researches on (I) the development of TiO2- and ZnO-based photocatalysts made through hydrothermal, sol–gel and flame spray pyrolysis processes, and (II) the development of suspension photoreactors with practical parameters influencing to photocatalytic activity. In both development approaches, the studies achieving the optimum of photocatalysis performance in high-yield degradation with associated parameters are explored, and the main causes of enhanced efficiency are described. Finally, from our view, opportunities for improvement on heterogeneous photocatalysts for water treatment are addressed.